KEPUASAN WISATAWAN TERHADAP WISATA KULINER DI OBJEK WISATA PANTAI INDAH SELATBARU KECAMATAN BANTAN KABUPATEN BENGKALIS - Novita Sari; Syofia Achnes (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Satisfaction is feeling happy and disappointed someone of comparing the performance of the product is perceived in the relationship and the performance of the products or services harapannya.jika lower than expectations, consumers will feel dissatisfied. If the performance as expected then the consumer will be satisfied, if the performance to exceed expectations, consumers will feel very puas.penelitian aims to determine Satisfaction Rating Against Culinary Available In Attractions Pantai Indah Selatbaru District Bantan District Bengkalis.This research uses descriptive quantitative method to examine the issue in the lift. The sample in this study were 100 respondents, taken using accidental sampling. While data collection techniques in this study using observation, questioner, and interviews. By using a Likert scale as a measure to determine the length of the short interval. With sub-variables on Expectations, Performance, Comparison, and the Confirmation / disconfirmation (Wilkie (1994) In the book Introduction to Tourism Marketing.From the results of research conducted in the field of research on the Satisfaction Rating Against Culinary At Attractions Pantai Indah Selatbaru District BantanBengkalis , with the theory of tourist satisfaction is divided into four sub variables: Expectations, Performance , Comparison , and the Confirmation / disconfirmation , the results field in the can that is on the satisfaction of travelers Against Culinary Travel Attractions in Pantai Indah SelatbaruBengkalis District Bantan included in the agree category.